Late Left Ventricular Outflow Tract Obstruction Following the Rastelli Operation: Expectations Out to 20 Years. (September 2016) - Cleveland, David C.; Kirklin, James K.; Pavnica, Jozef W.; Tresler, Margaret A.; Kukreja, Manisha; Dabal, Robert J.; Bryant, Ayesha S.; Isbell, Kayla D.; Romp, Robb L.
Background: Consensus is lacking regarding the optimal operation for transposition, ventricular septal defect, and pulmonary stenosis. Methods: Between 1968 and 2012, a total of 76 patients underwent the Rastelli procedure, with 52 mid- or long-term survivors. A bracketing analysis was used to estimate the likelihood of late left ventricular outflow tract obstruction (LVOTO). Results: Early mortality decreased over the period of study, with no hospital mortality since 2000. Among one year survivors, 10- and 20-year survival was 90% and 72%, respectively. Freedom from reoperation for LVOTO was 87% at 20 years, with no increase in risk among patients having the procedure before 5 years of age. Available late echocardiographic or catheterization data indicated mild or no LVOTO at a median of 14.3 years in a subset of 38 patients. Estimated freedom from major LVOTO at 20 years is bracketed between the estimate of 87% freedom from reoperation for LVOTO at 20 years and the 78% freedom from reoperation for LVOTO or cardiac death by 20 years. Conclusion: The Rastelli operation can be performed in the current era with an early mortality that approaches 0% and with 20-year survival that exceeds 70%. The late risk of important LVOTO appears to range from about 13% to 22% at 20 years, with no increase in risk among patients operated upon before the age of 5 years.